2016
DOI: 10.1039/c6ob02187e
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic enantioselective cascade Michael/cyclization reaction of 3-isothiocyanato oxindoles with exocyclic α,β-unsaturated ketones en route to 3,2′-pyrrolidinyl bispirooxindoles

Abstract: Cascade Michael/cyclization reactions between 3-isothiocyanato oxindoles and exocyclic α,β-unsaturated ketones are shown to proceed efficiently in the presence of a quinine-derived tertiary amino-squaramide catalyst and furnish 3,2'-pyrrolidinyl bispirooxindoles containing two spiro-quaternary and three contiguous stereocenters as a single diastereomer with excellent enantioselectivities (up to 99 : 1 er).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…[233] Mukherjee andc o-worker also realized an asymmetricd omino Michael/cyclization reactionb etween 3-isothiocyanatooxindoles 409 ande xocyclic a,b-unsaturated ketones 604.T he reaction afforded 3,2'-pyrrolidinyl bispirooxindoles 605 in high stereoselectivities (Scheme 156). [234] As imilar approach was also used by Du and coworkers,w ho recently realized ad omino Michael/cyclization reactionb etween 3-isothiocyanatooxindoles 409 and chalcone derivatives 606 using aq uinine-derived squaramide catalyst 608.T he domino protocol successfully provideds everal thiopyrrolidinyl spirooxindole skeletons (607a-d)i ng ood to excellent yields and stereoselectivities (Scheme 157). [235] Du andc o-workers also reported an asymmetric domino Michael/cyclization reactionb etween 3-isothiocyanatooxindoles 409 and maleimide derivatives 609 for the synthesis of pyrrolidonyl spirooxindoles 610 (Scheme 158).…”
Section: 231synthesis Of Indole-based Spirocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…[233] Mukherjee andc o-worker also realized an asymmetricd omino Michael/cyclization reactionb etween 3-isothiocyanatooxindoles 409 ande xocyclic a,b-unsaturated ketones 604.T he reaction afforded 3,2'-pyrrolidinyl bispirooxindoles 605 in high stereoselectivities (Scheme 156). [234] As imilar approach was also used by Du and coworkers,w ho recently realized ad omino Michael/cyclization reactionb etween 3-isothiocyanatooxindoles 409 and chalcone derivatives 606 using aq uinine-derived squaramide catalyst 608.T he domino protocol successfully provideds everal thiopyrrolidinyl spirooxindole skeletons (607a-d)i ng ood to excellent yields and stereoselectivities (Scheme 157). [235] Du andc o-workers also reported an asymmetric domino Michael/cyclization reactionb etween 3-isothiocyanatooxindoles 409 and maleimide derivatives 609 for the synthesis of pyrrolidonyl spirooxindoles 610 (Scheme 158).…”
Section: 231synthesis Of Indole-based Spirocyclesmentioning
confidence: 99%
“…Mukherjee and co‐worker also realized an asymmetric domino Michael/cyclization reaction between 3‐isothiocyanatooxindoles 409 and exocyclic α,β‐unsaturated ketones 604 . The reaction afforded 3,2′‐pyrrolidinyl bispirooxindoles 605 in high stereoselectivities (Scheme ) …”
Section: Multifunctional Catalystsmentioning
confidence: 99%
“…Based on the experimental results and the previous literature, [ 11f,15 ] a plausible mechanism relating to a stepwise manner for this asymmetric Michael/cyclization cascade reaction was proposed. In line with the well‐established mode of action of cinchona alkaloid derived bifunctional catalysts, the tertiary amine unit of the quinine deprotonates and orients the 3‐isothiocyanato oxindole 1a by forming hydrogen bond.…”
Section: Resultsmentioning
confidence: 97%
“…[ 10 ] It is well known that 3‐isothiocyanato oxindole is a widely used isatin derivative for the construction of spirooxindoles. [ 11 ] Very recently, some studies on thioaurone derivatives indicated that thioaurone derivatives were active exocyclic olefins. [ 12 ] Inspired by the above successful reports together with our previous successes in preparing diverse spirooxindoles, [ 13 ] we envisaged that a predicted [3+2] annulation could occur between 3‐isothiocyanato oxindoles and thioaurone derivatives to generate the spirooxindoles containing continuous spiral ring structures including an uncommon sulfur‐containing spirocyclic ring (Scheme 1, this work ).…”
Section: Introductionmentioning
confidence: 99%
“…76 The second approach comprises a cascade reaction with exocyclic enones, catalysed by chiral squaramides, to produce excellent results. 77 The third approach is the reaction with -ketophosphonates, 45 catalysed by bifunctional thiourea/tertiary amine catalysts, to afford excellent results (up to 91% yield, 20:1 d.r., and 99% ee). 78 A similar reaction comprising the Michael/cyclization cascade reaction of 3-isocyanato oxindoles and chalcones catalysed by chiral squaramides was reported by Du et al This 50 reaction afforded the final products in excellent yields (up to 99%) and stereoselectivities (up to >99:1 d.r.…”
Section: Scheme 46: Spirocyclization Reported By Shi and Xumentioning
confidence: 99%